Peran Sistem Pengendalian Internal Dalam Meningkatkan Akuntabilitas Pengelolaan Anggaran Pendapatan dan Belanja Desa di Kabupaten Kediri - ANAS, M.; FORIJATI, Rr.; LIANAWATI, DIAN (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This study aims to analyze and test the elements of the internal control system consisting of control environment, risk control, control activities, information and communication, and monitoring of the accountability of the management of the Village Budget (APB Desa) in Kediri Regency. The data in this study are primary data obtained through a research instrument in the form of a questionnaire developed based on indicators on each element of the internal control system. The population of this research is in the form of villages in Kediri Regency with a total of 343 villages, while the sample of this study was determined that 103 villages were selected randomly (random sampling). Data analysis to test the research hypothesis was carried out with multiple linear regression models with the SPSS version-23 application. The results of the study state that empirically the control environment and control activities partially have a positive and significant effect on increasing the accountability of APB Desa management in Kediri Regency, while risk assessment, information and communication, and partial monitoring have no significant effect on increasing the accountability of APB Desa management in Kediri Regency. Simultaneously all elements of the internal control sistem have a positive and significant effect on increasing the accountability of APB Desa management in Kediri Regency.